Empowering Creativity and Entrepreneurial Spirit: A Service-Learning Approach for MTs Students - Halim, Hendra; Sri Utami Permata; Teuku Meldi Kesuma; M. Ridha Siregar; Muhammad Haris Riyaldi; Burhanis Sulthan DM; Husaini (IJCS: International Journal of Community Service, 2024)
This community service program aimed to cultivate creativity and entrepreneurial spirit among 7th-grade students at MTsN 2 Aceh Besar through a Service-Learning approach. The program, conducted on May 23, 2023, at Aula Madrasah Terpadu Tungkob, involved interactive sessions and practical exercises to enhance students' understanding of entrepreneurship. The program included sessions on the definition and categories of entrepreneurship, brainstorming for business ideas using simple materials, the importance of entrepreneurship education, and basic financial recording for businesses. The activities encouraged students to think critically and creatively, providing them with practical skills for future endeavors. Collaboration between faculty members from Universitas Syiah Kuala, Universitas Sulawesi Barat, and researchers from the Pusat Riset Komunikasi Pemasaran, Pariwisata & Ekonomi Kreatif, Universitas Syiah Kuala, ensured a comprehensive and impactful program. The conclusion highlighted the success of the program in achieving its objectives and its positive impact on students and the community.